Penerapan Teknik Analogi dalam Layanan Informasi untuk Meningkatkan Keterampilan Analitik Siswa SMA - Izaac Resley (Pattimura University, 2017)
Students' analytic thinking skills through counseling services are essential. This ability is needed to solve the problems they face. Accordingly, an eclective model or method of counseling used to improve analytical skills is necessary. Technique analogies in information services can be used to improve students' analytic skills. The purpose of this research is to improve the information service process by practicing students' analytic skills. The research design uses PTK where the lecturer collaborates in research at the school where the BK teacher feels the problem in the information service he provides and then collaborates with the lecturer to solve it. The subjects of the study were students of class XI IPS1 SMA Negeri 5 Ambon as many as 35 people. The study was conducted in 2 cycles. Each cycle takes 4 meetings beyond the time used for pretest at the beginning of the first cycle, and 2 times the postes of analytic skill at once at the end of cycle I and again at the end of cycle II. This study uses a learning scenario as a guide for action implementation. The instruments used are service process observation sheets and inventory of analytic skills. The research produces qualitative and quantitative data analyzed by descriptive statistics and interpreted qualitatively. Research data is analyzed with three steps, namely: data reduction, data presentation, and decision making. The results show that the use of analogy techniques can be used in information services to improve students' analytic skills. Improved analytic thinking skills can be seen from the presence of students with low analytic skills in pre-cycle I tests increased in number on post cyclical I tests, and increased again at the post test cycle II. Such improvements occur also in students with analytic thinking skills are increasing in number to students with high analytic thinking skills when heading the cycle I test, and Cycle II postes. Based on the research findings, it is suggested to counseling teachers to: (1) use analogous techniques in the information services they provide, (2) make creative thinking skills as the objective of learning accompaniment.